2002
DOI: 10.1046/j.1466-822x.2002.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive phenology of a wet forest understorey in the Western Ghats, South India

Abstract: The reproductive phenology of 60 understorey species was monitored at monthly intervals for 20 months in a medium elevation wet evergreen forest in the Southern Western Ghats. The life forms monitored were herbs (including terrestrial orchids), shrubs and small trees. Flowering and fruiting were non‐uniform with a dry season flowering peak and wet season fruiting peak. Flowering in the understorey correlated negatively with rainfall. No significant correlation was detected for fruiting. Life forms had flowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Supra-annual flowering events (mass flowering once every two years) have been recorded in tropical rainforests of Costa Rica 20,21 and subtropical forests of Taiwan 5 . However, previous studies did not find supraannual flowering patterns in the forests of North East and South India 12,13,18 . Global climate change causes variation in the timing, duration and synchronization of phenological events in tropical forests 22,23 .…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…Supra-annual flowering events (mass flowering once every two years) have been recorded in tropical rainforests of Costa Rica 20,21 and subtropical forests of Taiwan 5 . However, previous studies did not find supraannual flowering patterns in the forests of North East and South India 12,13,18 . Global climate change causes variation in the timing, duration and synchronization of phenological events in tropical forests 22,23 .…”
mentioning
confidence: 71%
“…For instance, studies have shown that flowering and fruiting seasonality influences species demography, biotic interactions and other ecosystem processes [7][8][9][10][11] . Asia has a variety of forest types, including temperate forests, subtropical forests, montane evergreen rainforests and lowland tropical rainforests with varying degrees of seasonality [12][13][14][15][16] . The reproductive phenology of some of these forests has been extensively studied at the individual, population and community level 6,14,15,17 .…”
mentioning
confidence: 99%
See 3 more Smart Citations